IgG4‐related skin disease. (1st November 2014) - Tokura, Y.; Yagi, H.; Yanaguchi, H.; Majima, Y.; Kasuya, A.; Ito, T.; Maekawa, M.; Hashizume, H.
Summary: IgG4‐related disease (IgG4‐RD) is a recently established clinical entity characterized by high levels of circulating IgG4, and tissue infiltration of IgG4 + plasma cells. IgG4‐RD exhibits a distinctive fibroinflammatory change involving multiple organs, such as the pancreas and salivary and lacrimal glands. The skin lesions of IgG4‐RD have been poorly characterized and may stem not only from direct infiltration of plasma cells but also from IgG4‐mediated inflammation. Based on the documented cases together with ours, we categorized the skin lesions into seven subtypes: (1) cutaneous plasmacytosis (multiple papulonodules or indurations on the trunk and proximal part of the limbs), (2) pseudolymphoma and angiolymphoid hyperplasia with eosinophilia (plaques and papulonodules mainly on the periauricular, cheek and mandible regions), (3) Mikulicz disease (palpebral swelling, sicca syndrome and exophthalmos), (4) psoriasis‐like eruption (strikingly mimicking psoriasis vulgaris), (5) unspecified maculopapular or erythematous eruptions, (6) hypergammaglobulinaemic purpura (bilateral asymmetrical palpable purpuric lesions on the lower extremities) and urticarial vasculitis (prolonged urticarial lesions occasionally with purpura) and (7) ischaemic digit (Raynaud phenomenon and digital gangrene). It is considered that subtypes 1–3 are induced by direct infiltration of IgG4 + plasma cells, while the other types (4–7) are caused by secondary mechanisms. IgG4‐related skin disease is defined as IgG4 + plasma‐cell‐infiltrating skin lesions that form plaques, nodules or tumours (types 1–3), but may manifest secondary lesions caused by IgG4 + plasma cells and/or IgG4 (types 4–7).